1993
DOI: 10.1002/jmor.1052150203
|View full text |Cite
|
Sign up to set email alerts
|

Cranial osteogenesis in Monodelphis domestica (Didelphidae) and Macropus eugenii (Macropodidae)

Abstract: The pattern of onset and general rate of cranial ossification are compared in two marsupials, Monodelphis domestica (Didelphidae) and Macropus eugenii (Macropodidae). In both species a similar suite of bones is present at birth, specifically those surrounding the oral cavity and the exoccipital, and in both postnatal events follow a similar course. The facial skeleton matures more rapidly than the neurocranium, which is characterized by an extended period of ossification. Most dermal bones begin ossification b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
125
1
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(139 citation statements)
references
References 71 publications
11
125
1
2
Order By: Relevance
“…In particular, it has been observed that, in marsupials, the tongue and oral apparatus are quite advanced, that there is a massive chondrocranium, but limited cranial ossification, that the secondary palate appears to close relatively early, that differences in the rate and pattern of dental development exist, that the jaw joint undergoes a "recapitulatory" transformation postnatally, and that the brain is relatively underdeveloped at birth. Smith and colleagues in a series of studies have examined craniofacial development in marsupials (Clark and Smith, 1993;Smith, 1994Smith, , 1996Smith, , 1997Smith, , 2001aSmith, ,b, 2002Smith, , 2003Nunn and Smith, 1998;Vaglia and Smith, 2003;van Nievelt and Smith, 2005a,b). This work has alternated between detailed model-system approaches using Monodelphis domestica as a case study, usually in comparison with the well studied murid rodents, with broader phylogenetic surveys.…”
Section: Organogenesis In the Marsupial Craniofacial Regionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, it has been observed that, in marsupials, the tongue and oral apparatus are quite advanced, that there is a massive chondrocranium, but limited cranial ossification, that the secondary palate appears to close relatively early, that differences in the rate and pattern of dental development exist, that the jaw joint undergoes a "recapitulatory" transformation postnatally, and that the brain is relatively underdeveloped at birth. Smith and colleagues in a series of studies have examined craniofacial development in marsupials (Clark and Smith, 1993;Smith, 1994Smith, , 1996Smith, , 1997Smith, , 2001aSmith, ,b, 2002Smith, , 2003Nunn and Smith, 1998;Vaglia and Smith, 2003;van Nievelt and Smith, 2005a,b). This work has alternated between detailed model-system approaches using Monodelphis domestica as a case study, usually in comparison with the well studied murid rodents, with broader phylogenetic surveys.…”
Section: Organogenesis In the Marsupial Craniofacial Regionmentioning
confidence: 99%
“…Clark and Smith (1993) studied ossification sequence and pattern in Monodelphis domestica and Macropus eugenii. Cranial ossification patterns were also studied by Nesslinger (1956) and Frigo and Woolly (1996) in other marsupial species and confirm that the basic patterns presented by Clark and Smith for Monodelphis and Macropus are general patterns for marsupials.…”
Section: Organogenesis In the Marsupial Craniofacial Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the lamprey, marsupials are also critical to our understanding of heterochrony in neural crest cell development (Clark and Smith, 1993). Although marsupial mammals are born in a highly atricial state, the neonate must be capable of considerable functional independence.…”
Section: Neural Crest Cell Migration In Marsupialsmentioning
confidence: 99%